A spatiotemporal analysis of the driving forces behind the energy interactions of the Chinese economy: Evidence from static and dynamic perspectives. (15th January 2022) - Huang, He; Hong, Jingke; Wang, Xianzhu; Chang-Richards, Alice; Zhang, Jingxiao; Qiao, Bei
Abstract: China is the world's biggest energy consumer and carbon emitter; this is a great challenge to both global and national environmental security. To achieve energy conservation and emission reduction goals, it is essential to identify the driving factors that affect the energy interaction patterns of the Chinese economy. For this purpose, the spatial independent variable lag model (SLX) and structural decomposition analysis (SDA) methods were integrated to detect province-level consumption-based energy changes induced by five driving factors, and due consideration was also given to interregional spillover effects from both static and dynamic perspectives. The results of this study uncovered that energy intensity acted as a major driver for energy conservation both in the short- and long-terms, whilst the role of energy intensity in curbing energy consumption was weakened. In contrast, optimizing production structure offers the potential for big energy reductions and it was further noted that spillover effects contributed to both national and regional energy conservation. Consumption per capita and population size presented similar static effects on energy increases. The spillover effects of the former had a greater impact on energy consumption growth during the investigated period, whilst both static and dynamic processes of consumption structure failed to form fixed direct and spillover effects on energy use at the regional level. The findings of this study contribute to understanding the regional heterogeneity of driving forces for energy consumption and provide a solid foundation for making effective energy conservation regulations. Highlights: Static and dynamic models were developed to detect the energy consumption of China. Direct and spillover effects of driving factors were analyzed. Changes in consumption per capita showed positive spatial spillover effects. Production structure exhibited enhanced spillover effects over time. Consumption structure change failed to form fixed direct and spillover effects.